Aryl hydrocarbon receptor-regulated long non-coding RNAs: implications for glycolipid metabolism and prognosis in hepatocellular carcinoma - Xiao, Xiaoli; Liu, Yao; Qu, Xiaoyong; Liu, Logen; Li, Guo-Qing; Chen, Honghui; Zhou, Linlin; Liu, Yanping (Frontiers in Oncology, 2025)
BackgroundHepatocellular carcinoma (HCC) is a leading cause of cancer-related deaths with limited treatment options. Tumor metabolic disorder is elevated in HCC and activates the aryl hydrocarbon receptor (AHR), a transcription factor implicated in cancer progression. However, the role of AHR in regulating long non-coding RNAs (lncRNAs) and their impact on glycolipid metabolism remains underexplored.Materials and methodsWe investigated AHR’s influence on several HCC cell lines treated with the AHR ligand. RNA sequencing was performed to identify the differentially expressed (DE) lncRNAs and mRNAs. We analyzed the differences and then conducted functional pathway enrichment of the identified DE lncRNAs and mRNAs. Furthermore, we constructed co-expression networks of lncRNAs and mRNAs and performed survival analysis using The Cancer Genome Atlas (TCGA) data.ResultsRNA sequencing identified a substantial number of lncRNAs and mRNAs. DEG analysis identified the significant differences between them related to cancer progression, with pathways such as PI3K-Akt, VEGF, and PPAR signaling highlighted. A co-expression network was utilized to elucidate the lncRNA–mRNA interactions and their regulation of glycolipid metabolism.Survival analysis identified the AHR-regulated lncRNAs associated with poor prognosis, like ASAP1-IT1 and RMDN2-AS1.ConclusionThis study clarifies AHR’s role in regulating gene expression and metabolism in HCC, revealing novel lncRNA biomarkers and potential therapeutic targets that could aid HCC. Further research is needed to explore AHR’s effects on the regulation of glucose-lipid metabolism in HCC.